Meaning and scope of Treaty V (V 9) of Plotinus: a manual (ἐγχειρίδιον) of (neo-)platonic doctrine? - Martin de Blassi, Fernando G. (2025)
“Meaning and scope of Treaty V (V 9) of Plotinus: a manual (ἐγχειρίδιον) of (neo-)platonic doctrine?”. If it is true that Plotinus’ thought has been characterized by specialists as “the swan song of Greek philosophy” (López Eire 1973: 77) or the “glory of ancient philosophy” (Moreau 1970), this is largely due to the exegetical synthesis that the philosopher knew how to undertake with respect to the Platonic and Peripatetic doctrines, inherited from the Hellenic tradition. Now, Treaty V (V 9) of the enneadic set, according to the chronological order drawn up by Porphyry, seems to anticipate the display of erudition that the Neoplatonist master would later develop in other long-term works, belonging more pertinently to the teaching phase of Plotinus, which Porfirio places it in the middle and mature period. Thus, the present study aims to elucidate through a descriptive and critical analysis the philosophical frameworks that are thematized in the Treaty chosen for this occasion.